La risa contagiosa como estímulo incondicionado en condicionamiento clásico de actitudes hacia marcas comerciales (2021)
Background: the literature on classical attitude conditioning (CAC) does not report the use of human vocalizations to create or intensify attitudes. Objective: the purpose of the study was to verify the capacity of contagious laughter acoustic stimuli to originate positive attitudes towards neutral commercial brands when they are used as unconditional stimuli in CAC. Sample: 60 university students of both sexes aged between 18 and 30 years. Methodology: based on an intra-subject experimental design the CAC was applied, which involved simultaneous mating of neutral commercial brands with the more and the less contagious laughs. Five hypotheses were verified that compared explicit (measured with semantic differential) and implicit attitudes (measured by evaluative priming and electromyographic amplitude -EMC- of the zygomatic muscle) between pre and post conditioning and between commercial brands conditioned with more vs less contagious laughs. Results: with respect to the baseline, there were greater explicit post-conditioning attitudes towards commercial brands paired with more contagious laughter; no explicit attitudinal differences were found between brands conditioned with more vs. less contagious laughs. Only implicit attitudinal differences were evidenced between pre and post conditioning of the commercial brand paired with the most contagious male laughter. No differences were observed in the EMG amplitude of the zygomatic between pre and post conditioning or between commercial brands paired with more vs. less contagious laughs. Conclusions: contagious laughter has the capacity to transfer affective valence to neutral stimuli and agreement is not always observed between explicit and implicit postconditioning attitudes.